Clinicians with dyslexia: a systematic review of effects and strategies. (15th May 2015) - Locke, Rachel; Scallan, Samantha; Mann, Richard; Alexander, Gail
Summary: Background: For educators, an awareness of the impact of dyslexia on learners in the clinical workplace is vital: first, to be able to identify whether dyslexia may underlie certain traits and behaviours; and second, to be able to provide appropriate advice and support when dyslexia is identified. We reviewed the primary research evidence concerning the effects of dyslexia on clinicians (in or after training) in the workplace, and adaptive strategies ('workarounds') that are presently in use. Methods: A systematic search of literature was undertaken, followed by a narrative review of studies selected as meeting the inclusion criteria. The review used a priori research questions and focused on studies based on primary research evidence. Results: The review identified five key studies on qualified doctors or nurses with dyslexia. The impact of dyslexia on doctors can include: writing and calculating prescriptions, writing patient notes, and prioritising and making referrals. Strategies to minimise the effects of dyslexia include the use of adaptive technologies, the need for more time for mentors and supervisors, and an awareness of 'enabling' and 'disabling' environments. An awareness of the impact of dyslexia on learners in the clinical workplace is vital Discussion: The difficulties associated with dyslexia are varied and may be unexpected. Medical educators must therefore be aware of dyslexia and its impact. When supporting a trainee with dyslexia, there is guidance available but educators may struggle to identify strategies and resources that are evidence based, so further research is required.